A triboelectric nanogenerator design for harvesting environmental mechanical energy from water mist. (July 2020) - Chen, Yun; Kuang, Yicheng; Shi, Dachuang; Hou, Maoxiang; Chen, Xin; Jiang, Lelun; Gao, Jian; Zhang, Lanyu; He, Yunbo; Wong, Ching-Ping
Abstract: Mechanical energy is abundant in nature and its potential is yet to be fully explored. Despite intensive research, triboelectric nanogenerators (TENGs) can only collect the energy stored in bulk water; reports on harvesting environmental mechanical energy from small scale water sources, including water mist, are still lacking. In this research, which is inspired by how tapered micro-pillars collect water from the air, a solid-liquid TENG is proposed for harvesting mechanical energy from water mist. The contact area of a water droplet with a dielectric layer in the TENG was found to be the key factor influencing the performance of the TENG, and higher current and voltage were achieved using a tapered electrode with a large diameter or by setting multiple tapered electrodes in parallel. An increase in local ambient humidity was observed to cause a significant increase in the saturation voltage and reduce the voltage saturation time of the TENG. However, an increase in ambient temperature and the amount of unpurified water mist degraded the performance of the TENG. By optimizing the parameters, the TENG can produce a maximum open-circuit voltage of 9.5 V and a short-circuit current of 250 nA simultaneously. Seven commercial light-emitting diodes (LEDs) were easily lit by the TENG, and their brightness was sensitive to varied mist flow rates. These results could inform the design and fabrication of new self-powered humidity sensors and TENGs for collecting energy from air. Graphical abstract: A solid-liquid design of the TENG is proposed for collecting environmental mechanical energy in the water mist, and the TENG's performance is sensitively respond to the change in the mist flow rate. Image 1 Highlights: A novel solid-liquid design of the TENG was proposed for collecting environmental mechanical energy in the water mist. A higher current and voltage was obtained using a tapered electrode with large diameter or multiple parallel electrodes. TENG can easily light seven commercial LEDs whose brightness was sensitively respond to the change of mist flow rate.